The correlation of the severity of polysomnography with clinical assessment in cases of adult OSA in a tertiary hospital - V., Suresh; M., Gowri Shankar; D., Prabhu; S., Natarajan (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: Now days increasing number of people with sleep related breathing disorders especially obstructive sleep apnea are reporting every day in our institute, which is a tertiary referral centre. The objective was to correlate between clinical assessment andpolysomnographic features in an obstructive sleep apnea patient. Methods: A total number of 60 cases were analyzed retrospectively and those who were already clinically assessed and diagnosed as OSA by AHI>5/h in overnight PSG study. The clinical history, body mass index, Epworth sleepiness scale score and full night polysomnograpic data were obtained for all 60 cases. The age and gender differences in OSA cases were analyzed. The correlations between the BMI, ESS score, AHI, oxygen saturation sleep apnea, Epworth sleeps scale and apnea hypopnea index were explored. Results: Of the 60 cases OSA were analyzed, the mean (SD) age was 36.62 (±11.90) years and the men was mostly affected 96.7% than women only 3.3%. Of 60 cases, 30% of patients having mild form, 25% of patients moderate form, 45% of patients having severe form. The obese patients affected more 83.3% (50/60) than normal only 10% (6/60). The clinical symptom were analyzed by ESS score the normal 18.3%, mild 18.3%, moderate 28.3% and severe 35%. The mean oxygen saturation and heart rate of OSA patients were 72.35 (±11.47) and 69.90 (±15.26) respectively. Conclusions: The BMI and ESS score were positively correlated with severity of OSA. The oxygen saturation and heart rate were negatively correlated with OSA.